2019
DOI: 10.1155/2019/3894101
|View full text |Cite
|
Sign up to set email alerts
|

One-Carbon Metabolism Links Nutrition Intake to Embryonic Development via Epigenetic Mechanisms

Abstract: Beyond energy production, nutrient metabolism plays a crucial role in stem cell lineage determination. Changes in metabolism based on nutrient availability and dietary habits impact stem cell identity. Evidence suggests a strong link between metabolism and epigenetic mechanisms occurring during embryonic development and later life of offspring. Metabolism regulates epigenetic mechanisms such as modifications of DNA, histones, and microRNAs. In turn, these epigenetic mechanisms regulate metabolic pathways to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 94 publications
(98 reference statements)
0
12
0
1
Order By: Relevance
“…Methyl donor insufficiency constitutes a risk factor for weaned pups in growth retardation, delayed ossification, and cognitive deficits (14). Previous studies have mainly focused on the impact of methyl donor on neural tube defect, metabolism, and human and mouse offspring diseases (15)(16)(17). Recently, some studies have shown that the accumulation of methyl donor in cells is beneficial in improving muscle mass and betaine has a significant effect on skeletal myogenesis, such as proliferation and differentiation of myoblast in vitro and in vivo (18).…”
Section: Introductionmentioning
confidence: 99%
“…Methyl donor insufficiency constitutes a risk factor for weaned pups in growth retardation, delayed ossification, and cognitive deficits (14). Previous studies have mainly focused on the impact of methyl donor on neural tube defect, metabolism, and human and mouse offspring diseases (15)(16)(17). Recently, some studies have shown that the accumulation of methyl donor in cells is beneficial in improving muscle mass and betaine has a significant effect on skeletal myogenesis, such as proliferation and differentiation of myoblast in vitro and in vivo (18).…”
Section: Introductionmentioning
confidence: 99%
“…The altered methyl donor metabolism affects DNA methylation, histone modifications, and miRNAs. In addition, methyl donor challenges in humans, such as a LPD, alters epigenetically programed ES cell progenitor differentiation (Wu et al, 2019).…”
Section: Methyl Donor Perturbations Including a Maternal Low Proteinmentioning
confidence: 99%
“…Other locations within the human genome may be affected by changes in epigenetic marks as the result of diet fluctuations. For example, active H3K4me3 and repressive H3K27me3 maintain a pluripotent epigenetic state in ES and their progenitor cells (Wu et al, 2019). In hES cells, there are also abundant non-CpG methylated cytosines that may be important to early development (Lister et al, 2009).…”
Section: Methyl Donor Perturbations Including a Maternal Low Proteinmentioning
confidence: 99%
“…The methyl groups from one‐carbon metabolism can be utilized in different ways, including DNA methylation, histone modification and microRNA. [ 109 ] As shown in Figure 5 , SAM metabolized by methionine is the major methyl donor in cells and can transfer methyl groups to histones, DNA, RNA, and lysine and arginine residues in proteins. [ 110–112 ] Changes in the SAM level in cells affect methyltransferase activity and the histone methylation level.…”
Section: Functions Of One Carbon Metabolism In Mammals During Pregnancymentioning
confidence: 99%